Characterization of the sensory, chemical, and microbial quality of microwave‐assisted, thermally pasteurized fried rice during storage. Issue 9 (14th August 2020) - Montero, María Laura; Sablani, Shyam; Tang, Juming; Ross, Carolyn F.
Abstract : Abstract: Companies producing ready‐to‐eat (RTE) meals are looking for processing alternatives that allow them to gain presence in the supermarket chill section. Microwave‐assisted pasteurization systems (MAPS) offer the potential to produce safe, high‐quality foods. This research examined sensory, physical, chemical, and microbial changes in fried rice processed with MAPS and stored at 7 °C over a 6‐week storage period. Additional fried rice samples (cooked but not MAPS‐processed) were stored at –31 °C and were used as the control. Randomly selected trays of each type of rice were analyzed at 1, 4, and 6 weeks of storage. Aroma, appearance, taste/flavor, texture, mouthfeel, and aftertaste were evaluated by a semitrained sensory panel with rate‐all‐that‐apply questions. The type of rice treatment (MAPS or control) significantly influenced sensory attributes ( P < 0.05), with firm texture attribute of the egg being more intense in the MAPS‐rice compared to the control. In addition, storage time affected the sensory modalities of both rice samples, including aroma, appearance, and taste/flavor ( P < 0.05). No spoilage‐associated sensory attributes were detected in the MAPS‐rice during storage. At each examination point, various physical, chemical, and microbial analyses were conducted for the MAPS‐ and control rice. From the physical and chemical perspective, the MAPS‐rice did not present relevant changes over the period tested. Microbial growth was the main cause of spoilage of the MAPS‐rice; however, MAPS was able to extend the regular 5‐day shelf life of a chilled fried rice meal to 6 weeks, demonstrating the potential of this technology for the RTE industry. Practical Application: The findings of this study indicate that, by applying microwave technology to RTE fried rice, the shelf life can be extended from 5 to 7 days up to 42 days (6 weeks) when stored at 7 °C. This temperature closely mimics that of consumers' refrigerators in the United States. This study also shows the potential of working with a semitrained panel and RATA questions when characterizing sensory changes during storage.